Analisis Kualitas Tahanan Isolasi Pada Transformator Dengan Preventive Maintenance di Gardu Induk Garuda Sakti - Efryansah, Randra Agustio; Aini, Zulfatri (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2023)
Transformers work around the clock to maintain the stability of power distribution to the community. If inspections and maintenance are not done, it will cause problems such as disturbances and damage, one of which is a disturbance in transformer insulation resistance caused by high operation factors, temperature, leakage current, and equipment age that can cause a decrease or damage in insulation quality. Therefore, it is important to do regular maintenance, one of which is through preventive maintenance as an effort to know the quality of insulation resistance on transformers. In this study, preventive maintenance was carried out which includes four methods, namely polarization index, tangent delta, breakdown voltage, and voltage ratio, which are useful for knowing the feasibility of insulation resistance quality with the established standards and next preventive steps. This research took data at Garuda Sakti Main Substation, the data included testing data from polarization index, tangent delta, breakdown voltage, and voltage ratio. The results of the discussion were obtained in transformer 1 and 3 were still within the allowed standard, but there were some parts of transformer insulation that experienced a decrease in quality and preventive maintenance needs to be done. The preventive maintenance step from the deterioration of the polarization index is that cleaning between windings is needed to minimize deterioration. In the breakdown voltage, further examination is needed, such as purifying in order to increase the dielectric strength of oil in the transformer.Keywords - Transformer, Isolation Resistance, Preventive Maintenance, Polarization Index.